Insufficient levels of physical activity of adolescents associatewith sociodemographic, environmental and school factors Níveis insuficientes de atividade física de adolescentes associados a fatores sociodemográficos, ambientais e escolares - da Silva J.* (2018)
© 2018, Associacao Brasileira de Pos - Graduacao em Saude Coletiva. All rights reserved.This study investigated the associations between the level of physical activity with sociodemographic, environmental and academic factors of adolescents. Two thousand five hundred and forty-five adolescents aged between 14 and 18 from Florianópolis and neighboring cities participated in this study. The short version of the International Physical Activity Questionnaire (IPAQ) was used. The prevalence of inactive adolescents was 48.6%, being higher among females (53.9%). For girls, physical inactivity was associated with the lack of appropriate and free places for physical activity (OR = 1.30 95% CI 1.05 to 1.82), with no influence of other variables. For boys who had no professional activity (OR = 1.54 95% CI 1.14 to 2.08), less educated mothers (OR = 0.41 95% CI 0.27 to 0.75), or graduate mothers (OR = 0.35 95% CI 0,17-0,73), living in major cities (OR = 1.64 95% CI 1.17 to 2.31) and low socioeconomic classification when compared to the average (OR = 0.69 95% CI 0.49 to 0.97) were more prone to physical inactivity. It was observed that the socio-demographic variables were associated with the inactive behavior of boys and environmental variables were associated with the physical inactivity of girls. Among the academic factors, only having to repeat a year was associated with inactivity, and only for girls.